Case Report: Antiangiogenic Therapy Plus Immune Checkpoint Inhibitors Combined With Intratumoral Cryoablation for Hepatocellular Carcinoma - Li, Xin; Xu, Jiahua; Gu, Xiaoqiang; Chen, Ling; Wu, Qing; Li, Hongwei; Bai, Haoran; Yang, Jinzu; Qian, Jianxin (Frontiers in Immunology, 2021)
Background: Hepatocellular carcinoma (HCC) is a common gastrointestinal malignancy with high incidence and poor prognosis. Common treatment methods include surgery, transcatheter arterial chemoembolization (TACE), ablation, and targeted therapy. In recent years, combination treatment with antiangiogenic therapy and immune checkpoint inhibitors has made great progress in the treatment of advanced HCC. Here, we report the case of a patient with HCC who achieved a durable benefit from anti-vascular therapy and immune checkpoint inhibitors combined with intratumoral cryoablation. Main Body: A 38-year-old male patient initially presented with severe abdominal pain that was identified as an HCC rupture and hemorrhage by computed tomography (CT). The patient underwent emergency surgery and postoperative pathology confirmed HCC. The patient received prophylactic TACE after surgery. Unfortunately, three months after surgery, the patient developed multiple liver metastases. Subsequently, he received systemic anti-vascular therapy and immune checkpoint inhibitors combined with intratumoral cryoablation. After treatment, the patient achieved extensive tumor necrosis and the disease was effectively controlled. Conclusions: Anti-angiogenic therapy and immune checkpoint inhibitors combined with cryoablation can induce a powerful and effective systemic anti-tumor immune response, which is worthy of further research.